Consummate-Love Of Evelyn Salt In Philip Noyce's Salt Movie (2010): A Psychoanalytic Approach - Hastutiningsih, Arum Dwi (2012)
The problem statement of this study is how Consummate-Love of Evelyn Salt influences her personality in Phylip Noyce's SALT movie. The object of the research is the movie entitled SALT, directed by Phylip Noyce published in 2010. The researcher uses Sigmund Freud's psychoanalysis theory. The study belongs to qualitative study in which the writer uses two data sources, namely primary data source and secondary data source. The primary data source is SALT movie itself and the secondary data is the other source related to the analysis such as the aouthor biography, books of literary theory and also psychological books, particularly related to the psychoanalysis theory of Sigmund Freud. The method of the data collection is library research. The technique of the data analysis is descriptive analysis. From the result analysis, it can be drawn by some conclusion. Firstly, the element of the movie present a good unity. It consist of exposition, complication, climax and resolution. Secondly, the consummate-love of Evelyn Salt influences her to do something under her sense. As the work Ego, Evelyn fulfills the Id demand. Nevertheless, her superego can differentiate what is true and false.